Mastering civility a manifesto for the workplace - Porath, Christine Lynne (Grand Central Publishing, 2016)
From the leading authority on workplace incivility, Christine Porath, shows why it pays to be civil, and reveals just how to enhance effectiveness in the workplace and beyond by mastering civility